Implementasi Metode Waterfall dalam Sistem Informasi Rekuitmen Karyawan pada PT. Automobil Jaya Mandiri berbasis WEB - Joko Dwi Mulyanto; Supriatiningsih Supriatiningsih; Indriyanti Indriyanti (Jurnal Teknik dan Science, 2025)
The recruitment of PT Automobil Jaya Mandiri Purwokerto employees is the determination of a human resource management plan related to the large number of employees needed by PT Automobil Jaya Mandiri Purwokerto. PT Automobil Jaya Mandiri Purwokerto is one of the companies engaged in 3S automotive (Sales, Service, Spare Parts). PT Automobil Jaya Mandiri Purwokerto sometimes opens employee recruitment, but still applies manual systems such as applicant registration, selection tests, and recording applicant data. For this reason, a website-based employee recruitment system was created using the waterfall method in which there are several stages, namely software requirements analysis, design, program code creation, testing and support or maintenance to help disseminate information, add employees and assist manager performance. Meanwhile, the data modeling uses a structured method, namely Entity Relationship Diagram (ERD) to describe the data model and Logical Record Structure (LRS) makes it easier to define file specifications. This information system application on employee recruitment is a solution to be able to disseminate information about employee recruitment and selection online and can assist managers in managing payment data and transactions.